Challenges of Indonesian Christian Religious Education in the Industrial Era 4.0 - Kristian Sukatman; Piter Imanson Damanik (International Perspectives in Christian Education and Philosophy, 2024)
The coronavirus pandemic has accelerated the evolution of education towards 21st-century learning in alignment with the Industry 4.0 era. Educators are confronted with three key aspects: life and career skills, learning and innovation, and information media and technology. They must continuously update their knowledge and skills to meet the needs of the millennial generation. Technology has become integral, influencing learners' cognition and skills. Pre-pandemic, educational institutions had leveraged technology, yet challenges regarding infrastructure and human resource readiness emerge in online learning implementation. Teachers need to be innovative in designing remote learning tailored to student needs, supported by adequate technology. Interactive online learning enhances student motivation. Learning media serves as a crucial link, aiding in achieving learning objectives. Specific challenges also arise concerning the curriculum, emphasizing the significance of educational philosophy. In the context of Christian education, integrating faith and knowledge and considering spirituality are vital to producing academically and morally competent alumni. Challenges faced by Christian education in Indonesia include declining numbers of schools and financial constraints, with potential risks to Christian identity. Initiatives such as the takeover of Christian schools offer solutions.